An ultrathin cobalt-based zeolitic imidazolate framework nanosheet array with a strong synergistic effect towards the efficient oxygen evolution reaction. Issue 39 (1st October 2018) - Cao, Junhui; Lei, Chaojun; Yang, Jian; Cheng, Xiaodi; Li, Zhongjian; Yang, Bin; Zhang, Xingwang; Lei, Lecheng; Hou, Yang; Ostrikov, Kostya (Ken)
Abstract : A novel ultrathin cobalt-based zeolitic imidazolate framework hybrid nanosheet array exhibits enhanced electrocatalytic activity for the oxygen evolution reaction. Abstract : Development of highly efficient and stable zeolitic imidazolate framework (ZIF) nanosheets has recently received growing interest as alternatives to noble-metal electrocatalysts towards the oxygen evolution reaction (OER). Herein, we develop a novel vapor-phase hydrothermal growth strategy for in situ synthesis of ultrathin cobalt-based zeolitic imidazolate framework (ZIF-67) nanosheets grown on the surface of Co(OH)2 nanosheets vertically aligned on electrochemically exfoliated graphene (EG) foil. Ultrathin ZIF-67 nanosheets with a thickness of ∼5 nm are uniformly coated on the surface of a Co(OH)2 nanosheet array to form a 2D core–shell structure. Benefitting from the strong coupling and synergistic effects, the resulting EG/Co(OH)2 /ZIF-67 hybrid exhibits excellent catalytic activity for the OER in alkaline electrolytes, which only requires an overpotential of 280 mV to attain a current density of 10 mA cm −2 with a low Tafel slope of 63 mV dec −1 and high stability. Such high OER performance for the EG/Co(OH)2 /ZIF-67 hybrid is superior to that of commercial Ir/C catalysts and even better than that of all previously reported ZIF-based OER electrocatalysts. In situ Raman analyses demonstrate that under OER conditions, the Co–O species are converted into Co–OOH groups, which are responsible for the excellent catalytic activity of EG/Co(OH)2 /ZIF-67 in the OER.